Dhikr as a preventive attempt of sexual abuse of a child at school - Yashinta Rizky Ananda; Anastia Sabila Billiny (Seminar Nasional Bimbingan dan Konseling Jambore Konseling 3)
Students should gain comfort and safety while at school to make the learning process optimally. It’s continuous with the groundbreaking friendly child programme. The program designed to prevent violence and sexual abuse of children. But not a few case of sexual abuse that are found at the school for example, sexual abuse conducted by a friend, citizen schools, even predators who deliberately target children to become victims of sexual abuse. This can make the trauma even allow victims to become principals in the future if it doesn’t get the handling. The efforts that can be done to prevent acts of sexual abuse of children at the schools is by applying Dhikr. Dhikr applied before KBM begins. One of the benefits of Dhikr is to strengthen the heart and body from any kind of negative behavior e.g. from sexual abuse. As for the subject matter presented inthis article covers a few things, this form of sexual abuse that can occur at school, due to sexual abuse, Dhikr as preventive therapy of sexual abuse. Conclusion the author in this article so that the child is able tofortify themselves by way of morning Dhikr before KBM started for the prevention of sexual abuse.